Model pembelajaran multiple intelligences pendidikan agama Kristen bagi anak dalam menghadapi era society 5.0 - Sugijanti Supit (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
This paper discusses the multiple intelligences learning model's contribution to children's Christian religious education.Â The concept of the era of Society 5.0 motivates Christian religious education to improve itself to face the challenges and opportunities that exist through the multiple intelligences learning model. This objective is achieved using a qualitative description method with a literature review approach. The contribution of multiple intelligences learning presents critical, creative, and innovative work as the capital of Christian religious education equipped with digital technology skills without leaving the essence of Christian religious education. The challenges of the era of Society 5.0 will allow children's Christian religious education to proclaim values as a Christian characteristic that produces challenging and God-fearing learners.Â AbstrakTulisan ini membahas tentang kontribusi model pembelajaran multiple intelligences dalam pendidikan agama Kristen anak.Â Konsep era society 5.0 memotivasi pendidikan agama Kristen untuk membenahi diri dalam rangka menghadapi tantangan dan peluang yang ada melalui model pembelajaran multiple intelligences. Tujuan ini dicapai dengan menggunakan metode kualitatif deskripsi dengan pendekatan kajian pustaka. Kontribusi pembelajaran multiple intelligences menghadirkan karya kritis, kreatif dan inovatif sebagai modal pendidikan agama Kristen yang dilengkapi dengan keterampilan digital teknologi tanpa harus meninggalkan esensi pendidikan agama Kristen. Tantangan era society 5.0 akan menjadi peluang bagi pendidikan agama Kristen anak mewartakan nilai-nilai sebagai ciri khas Kristen yang menghasilkan nara didik yang tangguh dan takut akan Tuhan.